The pathogen’s playbook in cancer: from oncogenesis to progression - Cai, Hongzhou; Yang, Shaozhe; Wang, Ruizi; Li, Ruixin; Liu, Yihan; Chen, Ruzhou; Hu, Yun; Li, Ziwei; Zheng, Jinzhou; Sun, Xuan; Zhou, Guoren (Frontiers in Oncology, 2026)
Globally, around 15–20% of cancers are linked to microbial infections, involving viruses, bacteria, and fungi, each with distinct pathogenic features. Advanced multi-omics technologies have confirmed tumor-specific microbial communities within tumor tissues. This review categorizes microbes by their action mechanisms in cancer biology: one group (e.g., Helicobacter pylori, HPV, Aspergillus species) directly induces tumorigenesis via DNA damage, repairing pathway disruption, oncoprotein expression, and carcinogenic metabolite production; the other group (e.g., Fusobacterium nucleatum, HIV, Candida albicans) modulates tumor progression by regulating the tumor microenvironment, enhancing tumor cell chemoresistance, or suppressing anti-tumor immunity. Additionally, this review also explores clinical translation potential, highlights research challenges, and proposes future directions to support precision oncology advancement.